The color characteristics of components of vegetable semi-finished product before freezing - Одарченко, Андрій Миколайович (Technology audit and production reserves, 2013)
The color of products is an important feature of their trade look and competitiveness. Today, the instrumental methods of researches are recommended to carry out the quality assessment of products, as it allows to mark out different quantitative indexes. The colorimetric method has helped to distinguish color parameters for the components of vegetable semi-finished products, used for the first and second courses, which are responsible for its formation. These products include table beet, carrot and sweet pepper, depending on the processing modes and methods before their freezing. There was determined the effect of drying and trunk operations on the color index, color tone, colorimetric purity of the main components of vegetable semi-finished products, used for the first and second courses. It is noted that during the drying process the color tone of investigated samples changes with respect to the standard. However, compared to the effect of trunk process on the color shift, the tone is less significant. Moreover, it was found that the drying process helps to partially restore the color tone of the investigated samples of table beet, sweet pepper.